‘Out of sight, out of mind’ - towards a greater acknowledgment of submerged prehistoric resources in Australian science-policy as part of a common heritage - Ward, Ingrid; Elliott, Michael; Guilfoyle, David (Frontiers in Marine Science, 2022)
There is growing awareness of the need for greater acknowledgement of underwater prehistoric cultural resources as part of management and regulation of the seabed around many maritime countries, especially those with large indigenous populations and history such as Australia. Prehistoric cultural places and landscapes inundated by Post-glacial sea-level rise on Australia’s continental shelf remain largely out-of-sight and out-of-mind, hence awareness and hence legal protection of this resource is lacking. There is a clear need for greater integration of archaeology and cultural heritage management within the marine sciences as well as a greater awareness of this resource as part of a common heritage more generally. This paper explores some of the dichotomies between Western and Indigenous cultures in valuing and managing the seabed. We argue that in developing science-policy, an attempt at least needs to be made to bridge both the gap between the nature and culture perspectives, and the jurisdictional divide between land and sea. Part of the answer lies in a convergence of Indigenous knowledge with Western science approaches, focused around our understanding of physical processes impacting past and present coastal landscapes and on the seabed itself. We explore several case studies from northern and Western Australia that are trying to do this, and which are helping to provide a greater appreciation of the inundated landscapes of the inner shelf as part of a common heritage.